Pembatalan Transaksi Secara Sepihak Melalui Marketplace dalam Perspektif KUH Perdata - Veronica Angeline Novisaputri (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Electronic commerce (e-commerce) has become a dominant trend in modern buying and selling transactions, offering easy access and efficiency. Marketplaces like Shopee act as intermediaries between merchants and buyers, providing fast, secure, and integrated transaction facilities. However, behind this convenience, significant legal issues arise, particularly regarding unilateral transaction cancellations by buyers through the refund feature. In practice, these refund requests are generally approved by the marketplace without thorough verification of the validity of the cancellation reason or the existence of the goods already shipped by the merchant. This study aims to analyze the legality of unilateral cancellations by buyers from the perspective of Indonesian civil law, with reference to the provisions of the Civil Code (KUHPerdata) and the concept of electronic contracts as stipulated in the Electronic Information and Transactions Law (UU ITE). The study uses a normative juridical approach by examining laws and regulations, legal literature, and analyzing two case studies involving merchants BZS and HK. The results indicate that unilateral cancellations by buyers without returning the goods constitute a form of breach of contract. This action not only violates the electronic contractual agreement established during the transaction but also causes financial and reputational harm to merchants. This phenomenon indicates weak legal protection for business actors in the e-commerce ecosystem, particularly regarding the bargaining power between sellers, buyers, and marketplace platforms. Therefore, strengthening fair and transparent digital dispute resolution mechanisms is necessary, including preventive legal protection to prevent losses and repressive protection to provide redress for injured parties. This step is crucial for realizing a healthy, balanced, and equitable digital trade ecosystem for all parties involved.